Exploring the Nanoscale Origin of Performance Enhancement in Li1.1Ni0.35Mn0.55O2 Batteries Due to Chemical Doping. Issue 16 (8th March 2023) - Thersleff, Thomas; Biendicho, Jordi Jacas; Prakasha, Kunkanadu Rajappa; Moreno, Elias Martinez; Jøsang, Leif Olav; Grins, Jekabs; Jaworski, Aleksander; Svensson, Gunnar
Abstract: Despite significant potential as energy storage materials for electric vehicles due to their combination of high energy density per unit cost and reduced environmental and ethical concerns, Co‐free lithium ion batteries based on layered Mn oxides presently lack the longevity and stability of their Co‐containing counterparts. Here, a reduction in this performance gap is demonstrated via chemical doping, with Li1.1 Ni0.35 Mn0.54 Al0.01 O2 achieving an initial discharge capacity of 159 mAhg −1 at C/3 rate and a corresponding capacity retention of 94.3% after 150 cycles. The nanoscale origins of this improvement are subsequently explored through a combination of advanced diffraction, spectroscopy, and electron microscopy techniques, finding that optimized doping profiles lead to an improved structural and chemical compatibility between the two constituent sub‐phases that characterize the layered Mn oxide system, resulting in the formation of unobstructed lithium ion pathways between them. A structural stabilization effect of the host compound is also directly observed near the surface using aberration corrected scanning transmission electron microscopy and integrated differential phase contrast imaging. Abstract : To improve the longevity and cycling stability of Co‐free lithium ion batteries based on layered Mn oxides, the ways in which chemical doping influences their electrochemical performance are explored. It is found that small amounts of Al dramatically improve performance and this is attributed to the stabilization of lithium ion pathways between the constituent subphases arising from improved structural and chemical compatibility.